POTENSI EKSTRAK ETANOL BERAS HITAM SEBAGAI PENURUN GULA DARAH PADA TIKUS NEFROPATI DIABETES - Arifah Sri Wahyuni; Rima Munawaroh (Universitas Muhammadiyah Semarang, 2015)
Anthocyanins contained in black rice bran (BBH) has been shown to have several properties, such as antioxidant and antihyperglycemic. The purpose of this study is to establish the levels of anthocyanins contained in BBH as well as measuring the ability of a decrease in blood sugar in diabetic rats nephropatic. The study was conducted with pre- and post-test design with control group design Twenty rats were divided into 5 groups. Preparation of alloxan induced diabetic rats by ip dose of 160 mg / kg body weight and blood glucose levels of mice were monitored for 21 days. Rats with diabetic nephropathy is used as a sample. Treatment with ethanol extract of black rice bran (EEBBH) doses of 50, 100, and 200 mg / kg performed for 14 days. Blood sugar levels are set at day-7, -10, and -14. Determination of total anthocyanin content using the pH difference method.The results showed that administration of anthocyanin-containing EEBBH total of 3.28 ± 0.34 mg / mL. Giving EEBBH dose of 200 mg / kg significantly decreased the levels of GD to 130.50 ± 31.86 mg / dL.Keywords: Black Rice Bran, diabetic nephropathy, antihiperglikemia